2018
DOI: 10.1063/1.5038183
|View full text |Cite
|
Sign up to set email alerts
|

Charging of an irregularly shaped particle in the sheath of an rf plasma

Abstract: The charging process of micrometer-sized irregularly shaped particles in the sheath of a radio frequency discharge is measured using a combination of long-distance microscopy and the phase-resolved resonance method. The applicability of the method is shown for a cylindrical zinc oxide particle by measuring its mass density. A particle with more complex geometry is compared to a spherical polymethyl methacrylate particle to investigate the charging of irregularly shaped particles in detail. The results are simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…On the other hand, the smallest enclosing sphere model reported by Asnaz et al predicted R = 2 39 based on the capacitance of the smallest enclosing sphere. Both the smallest enclosing and the orientation-averaged equivalent sphere are depicted in Fig.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…On the other hand, the smallest enclosing sphere model reported by Asnaz et al predicted R = 2 39 based on the capacitance of the smallest enclosing sphere. Both the smallest enclosing and the orientation-averaged equivalent sphere are depicted in Fig.…”
Section: Discussionmentioning
confidence: 92%
“…The morphology of the clustered particle determines the value of R σ , distinguishing between filigree and compact-shaped particles. Asnaz et al showed that, in the particular case of the anisotropic plasma sheath, the capacitance of the smallest enclosing sphere correctly predicts the charge for tetrapods 39 .…”
Section: Introductionmentioning
confidence: 99%
“…Later this vertical resonance method has been considerably refined by looking at the phase response to a periodic external force in addition to the amplitude response [25,26,56,57]. The phase response allows to determine the resonance frequency with highest accuracy and, hence, to address tiny changes in the interaction of the particle with the plasma or between particles.…”
Section: Vertical Resonancementioning
confidence: 99%
“…These instruments allow to achieve the same magnification as conventional microscopes but at a much larger working (observation) distance of about 15 cm. With their optical resolution, size measurements with an absolute accuracy of a few hundred nanometer are possible [57]. Thus, long-distance microscopes serve well for size measurements of large particles of a≈10 μm and especially for agglomeration processes and the structure of agglomerates [132] (see figure 2…”
Section: Size Diagnosticmentioning
confidence: 99%
See 1 more Smart Citation